2014
DOI: 10.1088/1612-2011/11/7/075001
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the thermal lens in 3 at.%Tm:KLu(WO4)2and microchip laser operation

Abstract: A comparative study of the thermal lensing effect is performed for monoclinic 3 at.%Tm:KLu(WO 4 ) 2 crystals cut along the three principal axes of the optical indicatrix, N p , N m and N g . Optical power, sensitivity factors and astigmatism of the thermal lens are determined. It is found that the thermal lens is differently signed for beam propagation along N p and N m (for m-and p-polarizations, respectively). In contrast, beam propagation along N g possesses a positive lens with nearly two-times reduced ast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 22 publications
1
12
0
Order By: Relevance
“…Indeed, if expressed as S/M mg , it equals only 4%. The thermo-optic properties of Tm,Ho:KLuW are summarized in Table 1, together with recent data for singly Tm-doped KLuW [21]. The crystal cut is along the N g -axis (light polarization E || N m ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, if expressed as S/M mg , it equals only 4%. The thermo-optic properties of Tm,Ho:KLuW are summarized in Table 1, together with recent data for singly Tm-doped KLuW [21]. The crystal cut is along the N g -axis (light polarization E || N m ).…”
Section: Resultsmentioning
confidence: 99%
“…DTs are typically cut along the growth direction, or b-axis || N p -axis of the optical indicatrix, generating a negative thermal lens that leads to the cavity instability [19]. Only recently it was shown that another cut, along N g -axis, can provide the desired mode stabilization and Tm:DTs microchip lasers were developed [20,21]. Later on, the potential for power scaling to multi-watt levels was confirmed [22].…”
Section: Introductionmentioning
confidence: 99%
“…For the considered I the modulation depth will be only 1.2% that is . This is related to the low astigmatism of the thermal lens for N g -cut Tm:KLuW crystals [28]. The peak power is shown in Fig.…”
Section: Resultsmentioning
confidence: 86%
“…It was shown that Tm:DTs are suitable for the monolithic laser concept [26,27], provided a special crystal cut for light propagation along the N g dielectric axis is chosen. For this cut, the desired mode stabilization in the plano-plano cavity is ensured by a positive and nearly spherical thermal lens [28]; these properties are not available for the crystal cut along the growth direction, the b-axis. The specific features of the microchip concept allowed us to achieve ~10-fold improvement in terms of output power and pulse duration as compared with a recent report on Tm:KLuW laser with a hemispherical cavity Q-switched with a graphene SA [24].…”
Section: Introductionmentioning
confidence: 99%
“…It was oriented for light propagation along the N g -axis. This crystal orientation was selected because it provides a positive thermal lens [15,27] required for stabilization of the laser mode in a plano-plano microchip cavity. Both m × p crystal faces were polished to laser quality and remained uncoated.…”
Section: Methodsmentioning
confidence: 99%